As bases metafísicas do conhecimento sensível na crítica da razão pura de Immanuel Kant - Costa, Marcos de Holanda (2011)
We analyze the sensible forms, namely, space and time, and their possible relationships with knowledge. We credit, as well, the following interrogative: as the fundamentals of sensibility, space and time, organize our knowledge since, only we can only consider the object of knowledge that which is intuited spatially and temporally? The issue raised by Immanuel Kant leads us immediately to another intriguing overlapping issue, that is, we can only have access to the phenomenon, but not the thing itself. By the facts, here our discussion.